RELATIONSHIP FAMILY AND MATERNAL FACTORS WITH INFANT AND YOUNG CHILD FEEDING AGE 6-23 MONTHS IN INDONESIA - Heidy Dayanti; Demsa Simbolon (Jurnal Riset Kesehatan, 2022)
The Infant and Young Child Feeding (IYCF) programs aim to improve the nutritional and health status, growth and development, and survival of children in Indonesia. Knowing the relationship between maternal factors and family factors in feeding infants and children under 6-23 months. This study used secondary data and analysis of the 2017 Indonesian Demographic and Health Survey (IDHS). The research design used was an analytic observational design using a cross-sectional type to determine the relationship between maternal factors and family factors in feeding infants and toddlers 6-23 months. The sample used is 4869 with a minimum sample of 790 samples. The unit of analysis for this study was all children who were born alive from all live births from mothers who had children under five years of age 6-23 months and children who were born alive and were the last child of a mother who had already had a birth. Data analysis used univariate, bivariate, and multivariate analysis. Multivariate analysis using multivariate logistic regression. The results found that most of the children had the practice of IYCF not according to the recommendations (72.2%). Factors related to IYCF practices are a place of residence, socioeconomic, parity, mother's education, and mother's age, while the most dominant factor related to IYCF practice is socioeconomic. It is necessary to improve education, socialization, and movements toward families, so that the community, especially mothers with children aged 6-23 months.